Immunosuppressants and Ischemic Postconditioning in the Management of Brain Ischemia in Rats: The Role of Pharmacologic and Nonpharmacologic Treatments - Altıntaş Aykan, Duygun; Yıldız, Buket Tuğan; Kazancı, Ülkü; Seyithanoğlu, Muhammed; Koca, Tuba; Ural, Alper (European Journal of Therapeutics, 2023)
Objective: Ischemic postconditioning in limb skeletal muscle may decrease the size of the cerebral hypoperfused area after stroke. We compared the effects of ischemic postconditioning with the effects of the pharmacologic agents infliximab and leflunomide in the management of stroke. Methods: Thirty-two rats were divided into four groups: postconditioning, infliximab, leflunomide, and saline (control). Global cerebral ischemia was induced by clamping the bilateral common carotid arteries for 20 min, and subsequently reperfusion was allowed for 2 h. Rats in the infliximab group received 7 mg/kg of infliximab immediately after and 6 h after the induction of stroke. Rats in the leflunomide group received 10 mg/kg of leflunomide immediately after and 6 h after the induction of stroke. In the postconditioning group, the unilateral limb muscle was clamped for 180 min immediately after the induction of stroke, and subsequently reperfusion was allowed for 120 min. Rats in the control group received saline immediately after and 6 h after the induction of stroke. Glutathione peroxidase, malondialdehyde, and ischemia-modified albumin were measured, and histopathologic evaluation of cerebral tissue was performed. Results: The area of hemorrhage was significantly decreased in the infliximab group. Loss of the gray matter–white matter boundary was significantly decreased in the infliximab and leflunomide groups. Brain glutathione peroxidase was significantly increased in the infliximab group. There were no significant differences between the infliximab, leflunomide, and postconditioning groups and the control group in serum malondialdehyde and ischemia-modified albumin Conclusion: Immunosuppression by infliximab and leflunomide, but not ischemic postconditioning, may attenuate brain ischemia–reperfusion injury. Although the curative effects of postconditioning treatment on brain injury were documented, the lengths of the postconditioning cycles are important for its efficacy.